Epidermal growth factor receptor (EGFR) mutations in small cell lung cancers: Two cases and a review of the literature. (May 2016) - Siegele, Bradford J.; Shilo, Konstantin; Chao, Bo H.; Carbone, David P.; Zhao, Weiqiang; Ioffe, Olga; Franklin, Wilbur A.; Edelman, Martin J.; Aisner, Dara L.
Highlights: We report a case of SCLC harboring a novel D855H point mutation in the EGFR gene. We report a case of SCLC demonstrating a L858R point mutation in the EGFR gene. We review the literature and note 59 reported SCLCs with EGFR mutations. Only 4 EGFR mutations would not have been identified based on recent Guidelines. These findings support the Guideline recommendations for EGFR testing in SCLC. Abstract: Activating mutations in the epidermal growth factor receptor ( EGFR ) gene are exceedingly rare in small cell lung cancer (SCLC). We present two cases of SCLC harboring EGFR mutations, one in an 82 year-old male smoker with a combined SCLC and adenocarcinoma with a novel D855H point mutation in exon 21, and the second in a 68 year-old female never smoker with the L858R point mutation in exon 21. The cases, accompanied by a review of the literature, highlight the importance of integration of clinicopathologic considerations and adherence to recently promulgated Guideline recommendations for molecular testing in lung cancer.